Some considerations on the syntax of expletive subjects in Old Venetan and the emergence of subject clitics (Atti del Sodalizio Glottologico Milanese, 2021)
Old Venetan varieties display different forms of third person subject pronouns. In particular, the reduced monosyllabic and asyllabic forms are stronglyrelated to the expletive subject function. Even if the reduced forms do not have the same distribution of subject clitics in Modern Venetan, it can be argued that these forms have become clitics before the other pronouns. The article takes into consideration the syntax of expletive subjects in Old Venetan in relation to the rise of subject clitics in these varieties.